Pelvic inflammatory disease: A silent threat to female fertility (International Seven Journal of Health Research, 2024)
Pelvic inflammatory disease (PID) is a clinical condition of significant importance, given its potential to generate serious sequelae if it is not properly identified and treated. Among these sequelae is infertility, the relationship between which and the presence of PID is well established. The incidence of infertility is particularly exacerbated by persistent, recurrent and inadequately treated infections, causing considerable psychological distress for the women and couples affected. A proactive approach to the early identification and treatment of PID is fundamental to mitigating the risk of infertility and its emotional repercussions. In addition, raising awareness of risk factors and adopting preventative measures are equally crucial in promoting women's reproductive health and reducing the incidence of PID-related complications.